2020
DOI: 10.1371/journal.pntd.0008040
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Salmonella enterica serovar  Typhi in Colombia, 2012–2015

Abstract: Salmonella Typhi (S. Typhi) is the causative agent of typhoid fever; a systemic disease affecting~20 million people per year globally. There are little data regarding the contemporary epidemiology of typhoid in Latin America. Consequently, we aimed to describe some recent epidemiological aspects of typhoid in Colombia using cases reported to the National Public Health Surveillance System (Sivigila) between 2012 and 2015. Over the four-year reporting period there were 836 culture confirmed cases of typhoid in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…Complications were noted among 9 of the 30 interviewed cases. When compared with other studies, the rate of complications was higher in this outbreak [ 34–36 ], most likely due to delayed presentation [ 22 , 37–39 ]. Over 70% of Zama Zamas in South Africa are illegal immigrants [ 40 ], which may result in hesitancy to seek health care.…”
Section: Discussionmentioning
confidence: 49%
“…Complications were noted among 9 of the 30 interviewed cases. When compared with other studies, the rate of complications was higher in this outbreak [ 34–36 ], most likely due to delayed presentation [ 22 , 37–39 ]. Over 70% of Zama Zamas in South Africa are illegal immigrants [ 40 ], which may result in hesitancy to seek health care.…”
Section: Discussionmentioning
confidence: 49%
“…This collection comprised 60 unique PFGE profiles ( Fig 1 and S1 Table ), including the most commonly circulating restriction patterns in Colombia (e.g., COINXX.JPPX01. 0008-0083-0115)[ 18 ]. Twelve isolates also originated from eight outbreaks confirmed by the health authorities (A-H; 8, 4, 24, 9, 5, 2, 6, and 8 patients per outbreak respectively) (Figs 1 and S1 ); more than one isolate were included from two of these outbreaks (D and G).…”
Section: Resultsmentioning
confidence: 99%
“…Pulsed Field Gel Electrophoresis (PFGE) is the conventional method for studying the genetic relationship between S. Typhi isolates in Latin America [16]. Using this method, we recently found that some S. Typhi isolates from Colombia shared indistinguishable PFGE patterns with organisms from Argentina, Chile, Perú, Venezuela, Brazil, and Guatemala, indicative of the circulation of common "continental" genotypes [17,18]. However, PFGE has limited discriminatory power to support subtyping and cannot identify genotype 4.3.1, other emerging genotypes, or AMR genes.…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming preponderance (339/402; 84.3%) of S. Typhi were susceptible to all tested antimicrobials. The organism showed the most resistance against ampicillin (30/402;7.5%), followed by nalidixic acid (23/402, 5.7%) [154].…”
Section: Latin Americamentioning
confidence: 99%